Spatial mechanisms of quality control during chaperone-mediated assembly of the proteasome - Eshita Das; Linh Le; Vladyslava Sokolova; James D. Orth; Soyeon Park (Nature Communications)
Abstract Cellular protein degradation requires a complex molecular machine, the proteasome. To mitigate the fundamental challenge of assembling the 66-subunit proteasome, cells utilize dedicated chaperones to order subunit addition. However, recent evidence suggests that proteasome assembly is not simply a series of subunit additions, but each step may be scrutinized so that only correct assembly events advance to proteasomes. Here, we find an unexpected mechanism of quality control (QC) during proteasome assembly—via the proteasomal nuclear localization signal (NLS). This mechanism specifically sequesters defective assembly intermediates to the nucleus, away from ongoing assembly in the cytoplasm, thereby antagonizing defective proteasome formation. This NLS, a bona fide proteasomal component, provides continuous surveillance throughout proteasome assembly. Even a single incorrect event activates spatial QC. Our findings illuminate a two-decade-old mystery in proteasome regulation; proteasomal NLSs, dispensable for proteasome localization, instead provide QC by compartmentalizing assembly defects to ensure that only correct proteasomes form.